Do females plastically adjust hatching asynchrony as a reproductive tactic in response to climatic cues? - Bizberg-Barraza, Iván; Rodríguez, Cristina; Drummond, Hugh (Animal behaviour, 2024)
Hatching asynchrony is understood as a female tactic that shapes family dynamics, but its adjustment mechanisms and adaptiveness remain unclear. Using 32 years of individual data on a Neotropical seabird, the blue-footed booby, Sula nebouxii, we examined variation in hatching asynchrony in relation to sea surface temperature, a proxy for food abundance, and hatching asynchrony's adaptiveness. Under warm sea surface temperature, signalling low food abundance, females extended laying interval, resulting in increased hatching asynchrony. Longer hatching asynchrony was associated with more probable and earlier brood reduction. When brood reduction occurred, longer hatching asynchrony improved females' prospect of breeding the next year but not their timing of laying or production of fledglings and recruits. By extending laying interval, female boobies increase hatching asynchrony to cope with poor food conditions by prompting early brood reduction, thereby reducing reproductive costs and enhancing the probability of breeding the next year. Understanding the temperature sensitivity of plastic reproductive traits is crucial for predicting organisms' responses and resilience to global warming. •Hatching asynchrony (HA) positively correlated with sea surface temperature (SST).•Females rapidly and plastically extended laying intervals in response to warm SST.•Longer hatch intervals increased the probability and earliness of brood reduction.•When brood reduction occurred, HA increased females' next year breeding probability.•HA did not affect females' number of fledglings or recruits produced the next year.